2013
DOI: 10.1111/jpr.12033
|View full text |Cite
|
Sign up to set email alerts
|

Does spirituality really matter?: A study on the potential of spirituality for older adult's adjustment to aging

Abstract: This study intended to analyze the indicators of adjustment to aging (AtA) and to investigate the latent constructs that can work as major determinants in spirituality for a cross-national older community-dwelling population. Questionnaires were completed to assess the participants' background information. Interviews were performed, addressing one core area: indicators of AtA. Complete data were available for 154 older adults from two nationalities (German and Portuguese), aged between 75 and 103 years (M = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The COVID-19 pandemic promoted negative emotions, and in this context older adults expressed frustration, which can be tackled with engaging activities ( Mukhtar, 2020 ). Literature indicated that engagement with life is related to being receptive to different perspectives and activities, often related to older adults’ personal interests ( Reichstadt et al, 2010 ; von Humboldt et al, 2013a , b , 2014 ; von Humboldt and Leal, 2014a , b , 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic promoted negative emotions, and in this context older adults expressed frustration, which can be tackled with engaging activities ( Mukhtar, 2020 ). Literature indicated that engagement with life is related to being receptive to different perspectives and activities, often related to older adults’ personal interests ( Reichstadt et al, 2010 ; von Humboldt et al, 2013a , b , 2014 ; von Humboldt and Leal, 2014a , b , 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the specific character of spirituality as an opportunity to develop throughout the whole life, including old age, is emphasized by Heszen-Niejodek and Gruszczyńska (2004), who point out that "spirituality is an attribute of every person" (own translation). Spirituality can be further specified in relation to areas in which it operates and manifests itself, such as, i.e., reflection, self-reflection, awareness and self-awareness, wisdom, faith, religion, meditation, contemplation, sensibility, a sense of strength and direct power, autonomy, and a sense of dignity and fulfillment; rational, emotional and perceptive sensitivity; worldview, the will to experience a valuable life filled with hope, plans, dreams, and visions (Von Humboldt et al, 2014).…”
Section: Spirituality From Psychological Perspectivesmentioning
confidence: 99%
“…It is argued that in church practices, spirituality matters as Humboldt, Leal and Pimenta (2014) state that it is 'the affirmation of life in a relationship with God, self, community, and the environment that nurtures and celebrates wholeness'. A theological intrinsic flowing from this embodiment shows that it would be underachieving for the churches to engage themselves in Salvokop being unaware that God is the owner of the mission (missio Dei), John 10:10b.…”
Section: Discerning An Alternative Theological Agenda For Future Ecclmentioning
confidence: 99%